Moore’s paradox in belief and desire - WILLIAMS, John N. (Institutional Knowledge at Singapore Management University, 2014)
Is there a Moore’s paradox in desire? I give a normative explanation of the epistemic irrationality, and hence absurdity, of Moorean belief that builds on Green and Williams’ normative account of absurdity. This explains why Moorean beliefs are normally irrational and thus absurd, while some Moorean beliefs are absurd without being irrational. Then I defend constructing a Moorean desire as the syntactic counterpart of a Moorean belief and distinguish it from a ‘Frankfurt’ conjunction of desires. Next I discuss putative examples of rational and irrational desires, suggesting that there are norms of rational desire. Then I examine David Wall’s groundbreaking argument that Moorean desires are always unreasonable. Next I show against this that there are rational as well as irrational Moorean desires. Those that are irrational are also absurd, although there seem to be absurd desires that are not irrational. I conclude that certain norms of rational desire should be rejected.